Nekaj o uporabi AdS/CFT v fiziki kondenzirane snovi - Ulaga, Martin (Matrika, 2020)
The article summarises some notable results from the fiels of the AdS/CFT correspondance. This is the duality or equivalence of a strongly interacting quantum field theory, equipped with a conformal symmetry, and the theory of gravitation in anti de Sitter space. Because of the form of this text only some of the conceptual ingredients of the duality with an emphasis on the "holographic cookbook" for transcribing physical quantities between the theories are listed. The article begins with a description of AdS spacetime and continues with the evaluation of simple correlators in a vacuum. The second half of this article sketches how temperature and other thermodynamic quantities, relevant for condensed matter physics, are introduced to the gravitational theory: temperature, entropy and charge density. The contents of this article are a synthesis of several works. The main source is McGreevy 2009, which forms the basis for the mathematical parts. For their usefulness in the context of this article and their considerable scope I also mention Zaanen in sodelavci 2015 and Hartnoll, Lucas in Sachdev 2018.
Keywords: anti de Sitter space; anti de Sitterjev prostor; conformal symmetry; konformna simetrija; kvantna teorija polja; quantum field theory; teorija gravitacije; theory of gravitation